Peran Kepemimpinan Islami Sebagai Upaya Optimalisasi Kinerja dan Kesejahteraan Karyawan di CV. Pratama Ekspedisi Kabupaten Pasuruan - Putri, Della Pratami; Suryaningsih, Sri Abidah (Universitas Negeri Surabaya, 2021)
Indonesia is a country with a Muslim majority in it. So it would be nice if a system was based on Islamic rules, including leadership. An organization can operate well if there are leaders and optimal employee performance. The role of a leader is very important and has a correlation in optimizing employee performance and employee welfare. The purpose of this study was to see the role of Islamic leadership in optimizing employee performance and employee welfare at CV. Pratama Ekspedisi of Pasuruan Regency. The research method used is a descriptive qualitative approach by collecting data with the interview method then analyzing and concluding the results of the data. This research results that the role of a leader who is Islamic is able to optimize the performance and improve the welfare of the employees of CV. Pratama Ekspeidisi of Pasuruan Regency.